Становлення і розвиток традиційного співоцтва на Слобідщині - Черемський, К. (Народна творчість та етнографія, 2006)
This article is clarifying some aspects of the development of such phenomena as traditional singing in Slobidshyna. This article also represents some well-ordered factual materials and gives its evaluation.